Interdisciplinary connections to special education important aspects to consider - Bakken, Jeffrey P.; Obiakor, Festus E. (Advances in special education ;, 2015)
This two-part volume addresses the specific area of interdisciplinary connections within special education research. Special education has transformed as a result of legislation, new trends and current research investigations. Currently, there is no comprehensive resource that effectively covers these advances. Part A sets the agenda for this two-part volume by addressing the challenge of why an interdisciplinary understanding is necessary and also outlines the benefits of adopting a multidisciplinary framework.